Angrynomics - Lonergan, Eric. (Blackstone Publishing, 2020)
In Angrynomics<\/em>, Eric Lonergan and Mark Blyth explore the rising tide of anger, sometimes righteous and useful, sometimes destructive and ill\-targeted, and propose radical new solutions for an increasingly polarized and confusing world. Angrynomics<\/em> is for anyone wondering, where the hell do we go from here?<\/p>
Keywords: Economics